Parasympathetic nervous system dysfunction, as identified by pupil light reflex, and its possible connection to hearing impairment - Wang, Yang; Zekveld, Adriana A.; Naylor, Graham; Ohlenforst, Barbara; Jansma, Elise P.; Lorens, Artur; Lunner, Thomas; Kramer, Sophia E. (Public Library of Science, 2016)
Context Although the pupil light reflex has been widely used as a clinical diagnostic tool for autonomic nervous system dysfunction, there is no systematic review available to summarize the evidence that the pupil light reflex is a sensitive method to detect parasympathetic dysfunction. Meanwhile, the relationship between parasympathetic functioning and hearing impairment is relatively unknown.